The BMI of men and not sperm parameters impact on embryo quality and the IVF outcome. (16th September 2012) - Anifandis, G.; Dafopoulos, K.; Messini, C. I.; Polyzos, N.; Messinis, I. E.
Abstract It has been reported that increased body mass index (BMI) of men influences fecundity but it is not clear if it impacts on sperm parameters. Whether or not BMI of men influence sperm parameters and subsequently in vitro fertilization (IVF) result remains to be clarified. The aim of the present study was primarily to investigate the relationship between the BMI of men and sperm parameters (volume, concentration and motility) and whether or not it impacts on embryo quality and IVF outcome. Secondly, to investigate the impact of BMI of both men and women, in combination with their age, on IVF result. Three hundred and one couples were categorized according to their BMI. Group 1 (n = 64, both men and women had BMI l ≤ 25 kg/m2), group 2 (n = 79, both men and women had BMI > 25 kg/m2), group 3 (n = 142, men had BMI > 25 kg/m2and their wives had BMI ≤ 25 kg/m2) and group 4 (n = 16, men had BMI ≤ 25 kg/m2 and their wives had BMI > 25 kg/m2). Overall (n = 301) BMI and age of men did not correlate with sperm parameters. Group 1 and group 4, regardless of the BMI of their women, demonstrated the highest quality of embryos and consequently the highest percentage of pregnancy. Furthermore, the score of the combination of both BMI and age of both men and women resulted in a threshold level of less than 800 with a relative high per cent of pregnancy. BMI of men does not correlate with sperm parameters, but influences the quality of produced embryos in such a way that impacts on pregnancy rate.